2D Sediment Transport Modelling in High Energy River – Application to Var River, France. (2016) - Zavattero, Elodie; Du, Mingxuan; Ma, Qiang; Delestre, Olivier; Gourbesville, Philippe
Abstract: Specific environments such as the French Mediterranean coastline are characterized by steep catchments associated to a climate affected by high intensity rainfall events (over 1000 mm/hour). In such costal catchments, development of human activities and urban developments is very challenging and requests to address properly the issue of vulnerability for both water resources and infrastructures. In addition, the coastal area is frequently characterized by complex relationships between underground resources, rivers and sea. Due to the geological and the morphological conditions, the sediment management is a main issue for local communities. Under specific conditions and with a clear understanding of performance limits, 2D hydraulic modelling is a meaningful approach that can provide an accurate view on the physical processes within the river such as morphological dynamic. This paper develops a suitable methodology to build a 2D surface water flow model, including sediment transport in the lower Var valley, France, with MIKE 21 FM (DHI) modelling system. A sediment transport model – MIKE 21 Sand Transport (ST) - is used to find out the movement of sediments along the river. MIKE 21 ST is interfaced with the hydrodynamic module, MIKE 21 Flow Model (FM), which simulates the water level variations and flow in response to a bunch of forcing functions. The results allow to understand the sediment transport along the Var river and to analyse the impacts on the river-aquifer exchange areas. This approach can lead to carry out a model able to simulate properly the behaviour of physical processes within the river bed.